Improving the nutrient quality of foods and beverages using product specific standards for positive nutrients and ingredients will help to increase mean population intakes toward dietary guidelines - Dötsch-Klerk, Mariska; Carvalho, Sara; Lawrence, Corrine F.; Willems, Julie I. (Frontiers in Nutrition, 2023)
Background A shift toward more sustainable diets, rich in plant-based foods and with fewer animal-derived foods, is needed and will lead to improved health and environmental benefits. Food industry needs to play a part and broaden the scope of product reformulation beyond the reduction of nutrients to limit to increasing ingredients and nutrients in line with dietary recommendations for a healthy sustainable diet. Methods The Positive Nutrition Standards (PNS) were defined to increase the consumption of recommended ingredients and nutrients. The PNS were set by translating WHO and Codex guidance into product group standards, considering the role of the product group in the diet. The potential impact of the PNS for vegetables, wholegrain and fibre was modeled using data from the US NHANES 2017–2018 survey, assuming that, foods consumed would be reformulated to meet the standards where relevant. Results The modeling showed that application of the PNS could increase mean population intakes by 30% for fibre, by more than 50% for vegetables and even double the intake of wholegrain. However, reformulation alone would not be sufficient to reach recommended intake levels. Conclusion The PNS described in this paper can help to increase intakes of relevant positive nutrients and ingredients. However, a multistakeholder approach is needed to encourage consumers to make additionally required dietary shifts to meet the recommendations for positive nutrients and ingredients.